Pengembangan Inovasi Pendidikan pada Sis Learning Centre di Jakarta - Richard Andrew; Rini Tri Hastuti; Theresia Viony Wijaya (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This research aims to develop educational innovation in informal sectors that globally change after the Novel Corona Virus 2019 pandemic. The research uses a qualitative method using Sis Learning Centre, located at Pantai Indah Kapuk, Jakarta as the research subject. The findings consist of brief explanations about the changes in the business ecosystem, educational support platform, educational evaluation system, sustainability effect, and brand competitiveness. In conclusion, Sis Learning Centre needs to digitize the education, adapt the educational pattern, concepting the new brand for the digital program, periodically training and development, curriculum evaluation, internal evaluation system and analyzing the potential new market and enhancing the brand competitiveness.